Academic Impact of Learning Activity Sheets (LAS) in Teaching Asian History at the Secondary Level - Ryan Ramolete Pecson (CV. Media Inti Teknologi, 2026)
Background: In today's educational environment, 21st-century learners excel with diverse, contextualized, and technology-driven instructional materials.Aims: The study assessed the impact of developed Learning Activity Sheets (LAS) on Grade 7 students' learning of Asian History in a secondary-level pilot school, using an experimental one-group pretest-posttest design.Methods: Initially, all students were pre-assessed using a 30-item teacher-made test. The three least mastered competencies were identified and targeted using LAS, involving 32 students who required intervention. After the validation of the LAS by three experts, pilot testing began. The activity sheets were implemented during the weeks focused on the least-mastered topics. A posttest was administered to compare academic performance before and after the intervention.Results: Student performance improved after LAS implementation, from 72.25 (did not meet expectations) to 88.91 (very satisfactory), supporting the intervention's effectiveness. The study recommended the broader use of LAS across the Social Sciences and other learning contexts via action research, with findings to be shared in professional development sessions, such as Learning Action Cell (LAC) meetings or in-service training (INSET).Conclusion: The study confirmed the effectiveness of the developed LAS in improving Grade 7 students’ academic performance in Asian History, thereby accepting the alternative hypothesis.